2021
DOI: 10.1177/15330338211004916
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TMEM47 Induces Tamoxifen Resistance in Human Breast Cancer Cells

Abstract: Background: Tamoxifen (TAM) is the eminent first-line drug for endocrine therapy of hormone receptor positive premenopausal breast cancer and reduces the risk of recurrence by ∼50%. However, many patients developed TAM resistance and their diseases recurred. Our previous study on transcriptome profile of TAM resistant breast cancer cells revealed that the TMEM47 is one of the most significantly differentially expressed genes. The mechanism of how TMEM47 is involved in TAM resistance was not known. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The binding of EGR1 to the NGFR promoter has been previously shown [18], suggesting that EGR1 might act in concert with ATF3 and tightly controls the expression of CD271 during phenotype switching. Finally, we investigated the potential regulation of general markers of melanoma (PD-L1, MET) and of additional mediators of stemness and phenotype switching in addition to NGFR, such as SOX9, ATF3 and TMEM47 [26][27][28][29][30][31][32] in RFP-positive (RFP) or RFP-negative (−) sorted cells four and eight days after sorting. We observed increased expression levels from day four to eight; ATF3 and NGFR, in particular, revealed a steady increase in expression levels (Figure S2C).…”
Section: Ngfr/rfp + Cells Are Enriched Upon Dabrafenib Treatment Refl...mentioning
confidence: 99%
“…The binding of EGR1 to the NGFR promoter has been previously shown [18], suggesting that EGR1 might act in concert with ATF3 and tightly controls the expression of CD271 during phenotype switching. Finally, we investigated the potential regulation of general markers of melanoma (PD-L1, MET) and of additional mediators of stemness and phenotype switching in addition to NGFR, such as SOX9, ATF3 and TMEM47 [26][27][28][29][30][31][32] in RFP-positive (RFP) or RFP-negative (−) sorted cells four and eight days after sorting. We observed increased expression levels from day four to eight; ATF3 and NGFR, in particular, revealed a steady increase in expression levels (Figure S2C).…”
Section: Ngfr/rfp + Cells Are Enriched Upon Dabrafenib Treatment Refl...mentioning
confidence: 99%
“…The binding of EGR1 to the NGFR promoter was previously shown 35 , suggesting that EGR1 might act in concert with ATF3 and tightly controlled the expression of CD271 during phenotype switching. Finally, we investigated the potential regulation of general markers of melanoma (PD-L1, MET) and of additional mediators of stemness and phenotype switching besides NGFR such as SOX9, ATF3 and TMEM47 [36][37][38][39][40][41][42] in RFP positive (RFP) or negative (-) sorted cells four and eight days after sorting. We observed increased expression levels from day four to eight, particular ATF3 and NGFR revealed a steady increase in expression levels (Figure S2C).…”
Section: Ngfr/rfp + Cells Are Enriched Upon Dabrafenib Treatment Refl...mentioning
confidence: 99%
“…It has been confirmed that TMEM47 is located in the NC_000023.11 region and includes three exons. Studies have shown that the gene is expressed in the bladder, adipose and 23 other tissues and found that the overexpression of TMEM47 may induce resistance in patients to certain chemotherapy drugs [51,52]. The four point estimates ( γGBN , γGBU , γGPF and γGF ) of γ for the gene are 0.4703, 0.4547, 0.4816 and 0.4847, and the 95% HPDIs or CIs derived by the GBN, GBU, PF and Fieller's methods are (0.0023, 1.2380), (0.0337, 1.3083), (0.0562, 1.2410) and (0.0557, 1.3896), respectively.…”
Section: Application To Mctfr Datamentioning
confidence: 99%